Pendampingan pengolahan limbah Kulit Kacang sebagai alternatif pupuk organik - Nining Wahyuni; Andi Muhammad Irfan Taufan Asfar; Andi Muhamad Iqbal Akbar Asfar; Asrina Asrina; A. Taufik Ishak (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2022)
The problem of quantity of peanut shell waste is still the main problem that has an impact on the pile of peanut shell waste in large quantities. As a peanut cultivation center, this is a critical issue in Bulu Ulaweng Village. The community reduces piles of peanut waste by burning or disposing it in the river. This method will undoubtedly cause air and water pollution, impacting environmental ecosystems, especially rivers. So, this community service is planned with the PKK Women's Group in Bulu Ulaweng Village, Patimpeng District, Bone Regency, South Sulawesi Province. The goal is to deal with the problem of waste peanut shells and improve the knowledge and skills of the partners. The method of implementing the activity includes counseling using Tudang Sipulung. The training is carried out offline (product manufacturing, packaging, and labeling) and provides solutions to the problems encountered. The community service activities' results show that partners can process peanut shell waste into organic fertilizer. The resulting product can be a superior product for Bulu Ulaweng Village. It can be an example for neighboring villages and other areas with the same problem of reducing peanut shell waste. Bulu Ulaweng Village cannot only overcome the accumulation of peanut shell waste problem but other villages too. Therefore, this activity aligns with the government's program to create healthy and prosperous villages as a form of sustainable development goals proclaimed by the government through villages.